Viable Sweetpotato Technologies in Africa (VISTA) Tanzania project - Grant, F. (International Potato Center, 2015)
This flyer provides highlights of the activities and strategies employed by the VISTA project in Tanzania, since it began in October 2014 until July 2015. The overall goal of this 3 year project, is to contribute to improved dietary diversity, food security and incomes in Tanzania, especially among households with children under five years of age. It is implemented in seven districts in Mbeya, Iringa and Morogoro Regions which are part of USAID’s Feed the Future (FTF) zones of influence. The flyer concludes by providing a way forward for the next year of implementation.